2019
DOI: 10.1136/oemed-2019-105849
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of workplace violence against healthcare workers: a systematic review and meta-analysis

Abstract: We aim to quantitatively synthesise available epidemiological evidence on the prevalence rates of workplace violence (WPV) by patients and visitors against healthcare workers. We systematically searched PubMed, Embase and Web of Science from their inception to October 2018, as well as the reference lists of all included studies. Two authors independently assessed studies for inclusion. Data were double-extracted and discrepancies were resolved by discussion. The overall percentage of healthcare worker encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
437
7
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(595 citation statements)
references
References 48 publications
42
437
7
20
Order By: Relevance
“…In the first study (2), the authors systematically searched PubMed, Embase, and Web of Science from their inception to October 2018, and included 253 eligible studies (with a total of 331,544 participants). 61.9% of the participants reported exposure to any form of workplace violence, 42.5% reported exposure to non-physical violence, and 24.4% experienced physical violence in the past year.…”
Section: Recent Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study (2), the authors systematically searched PubMed, Embase, and Web of Science from their inception to October 2018, and included 253 eligible studies (with a total of 331,544 participants). 61.9% of the participants reported exposure to any form of workplace violence, 42.5% reported exposure to non-physical violence, and 24.4% experienced physical violence in the past year.…”
Section: Recent Studiesmentioning
confidence: 99%
“…Verbal and physical violence against healthcare workers (HCWs) have reached considerable levels worldwide, and the World Medical Association has most recently defined violence against health personnel "an international emergency that undermines the very foundations of health systems and impacts critically on patient's health" (1). Two systematic reviews and meta-analyses published at the end of 2019 found a high prevalence of workplace violence by patients and visitors against nurses and physicians (2), and show that occupational violence against HCWs in dental healthcare centers is not uncommon (3).…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence (WPV) in healthcare settings has been drawing attention for over 20 years [2,[4][5][6][7][8] and has been reported in many places, including Europe [9], Asia [10][11][12], the U.S. [13], and the Middle East [14]. According to a recent review, the prevalence of WPV against healthcare workers was higher in Asian and North American countries than that in other countries [15]. Female nurses were reported to be the victims of verbal abuse more often than male nurses, and male nurses were reported to be more commonly the victims of physical abuse [7].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional survey indicated that 34.4% of healthcare workers reported verbal or physical violence in the preceding 12 months, along with 13.5% of physical assault [58]. A meta-analysis showed that the prevalence of healthcare workplace violence is especially high in Asian and North American countries [59]. On the contrary, patients are also afraid that an important diagnosis will be missed or delayed through laziness, or incompetence of the physicians [60].…”
Section: Discussionmentioning
confidence: 99%